Managing currency risk : how Japanese firms choose invoicing currency /: how Japanese firms choose invoicing currency. (2018) - Itō, Takatoshi, 1950-; Koibuchi, Satoshi; Sato, Kiyotaka; Shimizu, Junko
No abstract available